ANALYSIS OF RUSSIAN TRANSLATION of CHAPTER TITLES OF “A DREAM OF RED MANSIONS” FROM THE PERSPECTIVE OF ADAPTATION THEORY - Сыюэ Ху (Вестник Московского государственного областного университета: Серия: Русская филология, 2019)
The Adaptation Theory is adopted in this paper as the theoretical framework and develops a systematic analysis of the Russian translations in chapter titles of A Dream of Red Mansions (from the first chapter to the eightieth). Two editions of Russian translations are compared from levels of vocabulary and sentence structure. Each translation method used by the translator during the process of translation must adapt to a specific purpose. The chapter titles of A Dream of Red Mansions can be considered part of the novel, whose translation purpose is to realize the communicative function and to transfer aesthetic influence.